FORMULASI DAN UJI ANTIBAKTERI SEDIAAN SABUN MANDI CAIR EKSTRAK DAUN RAMBAI PADI (Sonneratia caseolaris L.) TERHADAP Staphylococcus aureus - Adhila Ghina; Fitri Handayani; Achmad Kadri Ansyori; Panji Ratih Suci; Erna Fitriany (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2024)
Rampai padi (Sonneratia caseolaris L.) grows along the coast Mahakam River in Samarinda. It was identified to contain flavonoids with, high potential as antioxidants and antibacterials. Previous studies have explored the content, pharmacological activity, and development of preparations. This study aimed to formulate the ethanol extract of rambai padi leaves (EEDRP) in liquid bath soap and to determine its pharmacological activity as an antibacterial (Staphylococcus aureus). The sample used is EEDRP which is formulated in liquid bath soap in three formulations, A (5%), B (10%), and C (15%). The results of the phytochemical screening of EEDRP contained flavonoids, phenolics, tannins, saponins, and steroids. The EEDRP can be formulated into a liquid bath soap that is homogeneous, has a characteristic odor, and is blackish-brown to dark green-gray. The pH test results on the 1st, 3rd, and 7th day met the quality requirements, namely pH 4-10, the foam height test which met the foam height requirements of 1 - 10 cm. The total plate number test result was 0 colonies/g. The antibacterial activity of EEDRP liquid soap in formula A (5%) had an inhibition zone of 4.11 mm, formula B (10%) of 4.17 mm, and formula C (15%) of 6.38 mm.